Mystery manifest: the triune God, figuratively speaking - Ramshaw, Gail (Fortress Press, 2025)
Ramshaw mines treasures of the Bible, patristic sermons, theological treatises, mystical reveries, liturgical texts, hymns, and poetry to craft a richly textured collection and framework for thinking about language used to describe the triune God. Liturgists, ministers, and theologians will find it an invaluable source of wisdom and inspiration-- Provided by publisher